2021
DOI: 10.1016/j.jpeds.2020.10.071
|View full text |Cite
|
Sign up to set email alerts
|

A Substantial Proportion of 6- to 12-Month-Old Infants Have Calculated Daily Absorbed Iron below Recommendations, Especially Those Who Are Breastfed

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…During complementary feeding, iron is mainly supplied through formula or breast milk, fortified cereals, and meat, which guarantees an optimal absorption due to its highly bio-available heme iron content. Even though Abrams et al recommended increasing the proportion of heme iron in animal products where feasible [91], it is essential to remember that the protein intake must be below 15% of the total energy intake up to 2 years old [81].…”
Section: Iron Status During the Complementary Feeding Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…During complementary feeding, iron is mainly supplied through formula or breast milk, fortified cereals, and meat, which guarantees an optimal absorption due to its highly bio-available heme iron content. Even though Abrams et al recommended increasing the proportion of heme iron in animal products where feasible [91], it is essential to remember that the protein intake must be below 15% of the total energy intake up to 2 years old [81].…”
Section: Iron Status During the Complementary Feeding Periodmentioning
confidence: 99%
“…Using the Feeding Infants and Toddlers Study 2016 database [93], Abrams et al [91] recently calculated the amount of consumed and daily absorbed iron among infants aged from 6 to 12 months, fed with different types of milk (breast, formula, or mixed feeding), considering the different iron bioavailability among dietary iron sources. The physiologic absorbed iron requirement was estimated to be 0.69 mg/day by applying a 10% absorption rate to the iron EAR (6.9 mg/day).…”
Section: Iron Status During the Complementary Feeding Periodmentioning
confidence: 99%
“…However, when researchers examined the 2016 FITS data for iron consumption and considered the estimated bioavailability of dietary iron sources to evaluate the proportion of infants whose calculated total daily absorbed iron fell below recommended amounts, they found that approximately 20% of exclusively formula-fed infants did not have enough absorbed iron to meet recommended amounts to support growth and erythropoiesis. 9 Although human milk is initially high in zinc that is readily absorbed, the concentration declines during the first Beef portions can be split up throughout the day, and textures can easily be modified for traditional feeding or baby-led weaning. Top row: pureed beef, ground beef, and shredded beef.…”
Section: First Foods Need To Be Nutrient Dense and Variedmentioning
confidence: 99%
“…Larger dietary doses are also necessary when conditions that promote iron losses (e.g., inflammation, chronic disease, occult gastrointestinal bleeding associated with exposure to cow-milk protein, food allergies, or infectious agents) are considered ( 26 , 27 ). A recent study by Abrams et al ( 28 ), using data from FITS, reported that daily iron absorption was below the recommended amount in 54.3% of 6–24-mo-old infants and ranged from 19.5% in exclusively formula-fed infants, to 95.8% in exclusively breastfed infants, with 72.2% in mixed-fed infants. The calculated mean iron absorption of 6- to 9-mo-old breastfed infants was lower than the estimated physiologic requirement (i.e., 0.27 mg/d vs. 0.69 mg/d, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The calculated mean iron absorption of 6- to 9-mo-old breastfed infants was lower than the estimated physiologic requirement (i.e., 0.27 mg/d vs. 0.69 mg/d, respectively). The authors concluded that “rates of low absorbed iron indicate that all infants may need monitoring for clinical evidence of low iron status” ( 28 ).…”
Section: Introductionmentioning
confidence: 99%